Hubungan Karakteristik Individu dan Riwayat Stroke dengan Kekuatan Otot pada Pasien Stroke - Hermawan, Stepanus Maman; Wihardja, Hany (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Stroke is the third leading cause of death worldwide. Serious long-term disability and paralysis is a burden forsurvivor stroke patients. Disability is caused due to muscle and nerve weakness in the upper and lower limbs.This study aims to identify the relationship between individual characteristic and history of primary stroke tomuscle strength in stroke patients in outpatient and inpatient units in General Hospitals, West Kalimantan. Thisresearch used a cross-sectional descriptive analysis approach using questionnaires and Manual Muscle Testing(MMT). The sample in this study were 99 stroke patients. The study was conducted in April to June 2018.Statistical test results showed a significant relationship between age (p = 0.026), gender (p = 0.029), andstroke history (p = 0.036) and muscle strength. Muscle strength can be increased with strengthening exercisesthat are repetitive and consistent. This exercise must be adjusted to the age, gender, and condition of theprevious muscle atrophy to preventing long-term disability.